Photodegradation of Phenol using TiO, Nanotubular thin film fabricated by Sonoelectromechanical anodization - Mohd Hasmizam Razali; Ahmad Fauzi Mohd Noor; Mahani Yusoff (Trans Tech Publications, 2015)
Photodegradation of phenol in aqueous solution was carried out using TiO2 nanotubular thin film. The TiO2 nanotubular thin film has been fabricated by sonoelectrochemical anodization process using a mixture of ethylene glycol and ammonium fluoride as electrolyte. The process was carried out at constant applied potential (20 V) for 90 minutes. After anodization the TiO2 nanotubular film was annealed at 500 °C for 2 hours and characterized using SEM and EDX to study morphology and chemical element compositions. SEM analyses revealed that the fabricated thin film had tubular structure with the diameter between 45 – 64 nm and 6.8 um in length composed of titanium and oxygen elements were determined by EDX. The fabricated TiO2 nanotubular thin film showed high photocatalytic activity with 80.70 % phenol degradation after 5 hours irradiation with UV light.